Cushing’s syndrome caused by ACTH precursors secreted from a pancreatic yolk sac tumor in an adult—a case report and literature review - Chang, Johnny Yau Cheung; Woo, Chariene Shao Lin; Chow, Wing Sun; White, Anne; Wong, Ka Chung; Tsui, Po; Lee, Alan Chun Hong; Leung, Eunice Ka Hong; Woo, Yu Cho; Tan, Kathryn Choon Beng; Lam, Karen Siu Ling; Lee, Chi Ho; et al. (Frontiers in Medicine, 2023)
Here, we report the first adult case of pancreatic yolk sac tumor with ectopic adrenocorticotropic hormone (ACTH) syndrome. The patient was a 27-year-old woman presenting with abdominal distension, Cushingoid features, and hyperpigmentation. Endogenous Cushing’s syndrome was biochemically confirmed. The ACTH level was in the normal range, which raised the suspicion of ACTH precursor-dependent disease. Elevated ACTH precursors were detected, supporting the diagnosis of ectopic ACTH syndrome. Functional imaging followed by tissue sampling revealed a pancreatic yolk sac tumor. The final diagnosis was Cushing’s syndrome due to a yolk sac tumor. The patient received a steroidogenesis inhibitor and subsequent bilateral adrenalectomy for control of hypercortisolism. Her yolk sac tumor was treated with chemotherapy and targeted therapy. Cushing’s syndrome secondary to a yolk sac tumor is extremely rare. This case illustrated the utility of ACTH precursor measurement in confirming an ACTH-related pathology and distinguishing an ectopic from a pituitary source for Cushing’s syndrome.